Treatment of Oral Conditions by 810 nm Diode Laser - AI-Mahdi, Akmam H. (Iraqi Journal of Laser, 2010)
When laser light incident on biological tissue, it is either reflected from thesurface of the tissue (e.g. the skin) or scattered inside the tissue or absorbed .The laser light will beabsorbed by water, hemoglobin and melanin. Absorption is also highly dependent on wave-length oflaser radiation. The absorbed light is converted into kinetic energy leading to laser effect that whenappropriately applied can produce reaction ranging from incision, vaporization to coagulation. Aim ofthe study: To evaluate the efficiency of diode Laser 810 ± 20nm in treatment of oral lesions. Methods:6 patients (2 females and 4 males) with different oral lesions were treated in the hospital of specializedsurgeries by the use of diode laser 810 nm, the lesions were: Apthous, Lichen planus, Pyogenicgranuloma, Second stage of implant. Results: The result of the study depended mainly on the c l i n i c alobservation during operation and in the follow up period. The results show that there was no pain, nobleeding, and no infection while the edema and necrosis at the operation site are present. Conclusion:Laser can be used to perform haemostatic surgery, decrease rate of infection and reduce post operativediscomfort.